Giants of contract law – Some personal reflections - PHANG, Hon. Andrew (Institutional Knowledge at Singapore Management University, 2022)
The law of contract may seem mostly technical and, on occasion, even overly theoretical. However, if one looks more closely at its foundations as well as scholarship, it is clear that contract law has much greater value to offer us. In that regard, the present essay has two main aims. The first is the give a brief account of the lives as well as scholarship of four giants of contract law whom we have lost in the past few years. Indeed, it may be said that their scholarship has contributed to the foundational bedrock of the law of contract as we know it today; a great debt of gratitude is owed to them. The second aim is to draw out some life lessons of more general application for us all.